Simone Weil: The Ethics of Affliction and the Aesthetics of Attention. Issue 2 (14th March 2020) - Thomas, Christopher
ABSTRACT: For Simone Weil the invocation of 'rights' to address extreme human suffering–what she calls 'affliction'–is 'ludicrously inadequate'. Rights, Weil argues, invite a response, whereas what the afflicted require is not dialogue but simply to be heard . For Weil, hearing the 'cry' of the afflicted is the basis of all justice. The task of such a hearing is given over to Weil's concept of attention, which demands an ethics of creative silence. This paper will argue that central to Weil's ethics of attention, and thus the way she thinks we should show compassion and act justly, is the Kantian aesthetic concept of disinterestedness . I will argue that whilst Weil is influenced by Kant in multiple ways, it is his aesthetics, rather than his normative moral theory, that is most at play in her own ethical theory of attention.